Peculiarities of sport motivation and sport satisfaction of young sportsmen in different branches of sports - Melinis, R.; Vilkas, A. (LASE Journal of Sport Science, 2018)
Background. Some conducted research (Gillet et.al. 2010; Lorimer, 2011) reveals that athletes` satisfaction and motivation have a large impact on their results. Therefore, sport coaches should be aware of the regularities of the expression of motivation characteristic of young athletes and the level of their satisfaction. Methods. The sample of the current research included 211 athletes divided into 5 groups. The athletes completed two questionnaires. The questionnaire concerning motivation for sport was devised on the basis of the Sport Motivation Scale (SMS, The Sport Motivation Scale; Pelletier et al., 1995) that is applied in Lithuania (Grajauskas, 2008). The athletes were also asked to fill in the Athlete Satisfaction Questionnaire compiled by Riemer and Chelladurai, which aimed at investigating the athletes` satisfaction with their participation in sports (Riemer, Chelladurai 1998). Results. Handball (IM - 4,47, EM - 3,96) and football players (IM - 4,41, EM - 3,93) had the strongest intrinsic motivation, whereas the athletes of individual sport branches had the weakest intrinsic and extrinsic motivation (IM - 4,15, EM - 3,63). Handball players seemed most satisfied with own performance in sport activity. The athletes of martial arts were least satisfied with their individual performance in sports. Conclusions. It was determined that athletes with high intrinsic motivation for doing sport activities giving them satisfaction and pleasure tend to evaluate their participation in sport more favourably. The athletes of martial arts were least satisfied with their participation in sport; therefore, their activity bore no sense for them. This shows the highest level of amotivation, which is associated with the loss of the meaningfulness of the activity.